1999
DOI: 10.1590/s1516-14391999000400008
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ceramic foams permeability using Ergun's equation

Abstract: SiC-Al2O3 ceramic foams with 30 to 75 pores per linear inch (ppi) were used to access the application of pore size obtained by image analysis to estimate the cellular materials permeability through Ergun's equation. Samples were sliced and the pore size distribution, cross-sectional porosity and pore density were evaluated as a function of the slice thickness based on optical and X-ray computerized tomography acquired images. The average pore sizes were used to calculate permeability constants (k1 and k2) of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 8 publications
2
65
0
2
Order By: Relevance
“…Permeability is a measure of the ability of a porous medium to transmit fluids through its interconnected pores or channels. Two permeability parameters, known as the Darcian, k 1 , and the non-Darcian, k 2 , permeability constants, can be found in the Forchheimer equation (Innocentini et al 1999). The Darcian permeability constant is related to the pure laminar flow properties while the non-Darcian permeability constant represents deviations from laminar flow.…”
Section: Porosity and Permeability Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Permeability is a measure of the ability of a porous medium to transmit fluids through its interconnected pores or channels. Two permeability parameters, known as the Darcian, k 1 , and the non-Darcian, k 2 , permeability constants, can be found in the Forchheimer equation (Innocentini et al 1999). The Darcian permeability constant is related to the pure laminar flow properties while the non-Darcian permeability constant represents deviations from laminar flow.…”
Section: Porosity and Permeability Constantsmentioning
confidence: 99%
“…Ergun proposed empirical expressions to describe the two permeability parameters for packed columns made of grains (Innocentini et al 1999;Nield and Bejan 2006). These expressions are:…”
Section: Porosity and Permeability Constantsmentioning
confidence: 99%
“…In this context, it is interesting to select available routes for processing macroporous ceramics in order to find an inexpensive, environmentally friendly and suitable method for the manufacture of porous supports. An extensive review on processing techniques of macroporous ceramics and its relationship to control the porosity was made by Studart et al 64 Further information can be found elsewhere [65][66][67][68][69][70] . A more recent and innovative method to fabricate ultra thin MIEC membranes, different of those proposed for planar configurations, is the formation of asymmetric hollow fibers via an immersion induced phase inversion and sintering techniques.…”
Section: Supported Miec Membranesmentioning
confidence: 99%
“…There have been attempts to revise Ergun's equation for non-spherical and non-uniform particles size bed (Dolejs and Machac, 1995;Gunarathne et al, 2014;Innocentini et al, 1999). Some of the authors refitted Ergun's equation for a specific material and obtain new values for constant (K 1 and K 2 ) but retained the overall structure (the porosity correlation-Eqns.…”
Section: Introductionmentioning
confidence: 99%